2021
DOI: 10.3390/biology10070616
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Food Supplementation in Microcirculation—A Comprehensive Review

Abstract: (1) Background: Cardiovascular disease (CVD) is a major public health concern worldwide and a key cause of morbidity and mortality in developed countries. Accumulating evidence shows that several CVD forms are characterized by significant microcirculatory dysfunction, which may both cause and be caused by macrovascular disease, often preceding clinical manifestations by several years. Therefore, interest in exploring food supplements to prevent and restore microcirculation has grown. Given the continuous need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 183 publications
(197 reference statements)
0
12
0
Order By: Relevance
“…In Europe, ginseng is an available and well-known ingredient. It usually appears in a dried form, extracts, or dietary supplements [195]. According to EFSA, Panax ginseng was used as the food of food ingredient before the year 1997; thus, it is not a novel food product [104] (Table 2).…”
Section: Ginseng (Panax Ginseng Cameyer)mentioning
confidence: 99%
“…In Europe, ginseng is an available and well-known ingredient. It usually appears in a dried form, extracts, or dietary supplements [195]. According to EFSA, Panax ginseng was used as the food of food ingredient before the year 1997; thus, it is not a novel food product [104] (Table 2).…”
Section: Ginseng (Panax Ginseng Cameyer)mentioning
confidence: 99%
“…Hamamelis virginiana L., also known as witch hazel, is a shrub that belongs to the Hamamelidaceae family [ 63 , 64 ]. Preparations from Hamamelis leaves, bark, and twigs, present in extracts, tinctures, creams, and salves, are utilized to treat dermatological (sunburn, irritated skin, and atopic eczema) and vascular disorders (hemorrhoids, varicose veins, and phlebitis), highlighting the fact that this plant has a wide range of biologically active substances [ 64 , 65 , 66 ].…”
Section: Phytotherapy In Skin Diseasesmentioning
confidence: 99%
“…Leaves contain 3–10% of tannins (a mixture of gallotannins and condensed catechins–procyanidins); notably a small amount of hamamelitannin; phenolic acids (caffeic and gallic acids); flavonoids such as kaempferol, quercetin, quercitrin, and isoquercitrin; and essential oil [ 26 , 64 , 67 , 68 , 69 ]. Numerous in vitro and in vivo studies have shown that this plant has antitumoral, antioxidant, anti-inflammatory, antibacterial, antiviral, and antimutagenic activity [ 63 , 64 , 68 , 69 , 70 ]. For instance, the extract of witch hazel leaves and small twigs can decrease the amount of IL-8 produced by fibroblast cells [ 71 ].…”
Section: Phytotherapy In Skin Diseasesmentioning
confidence: 99%
“…[9][10][11] Whole plant parts of Bua Bok are valuable raw materials for pharmaceutical, cosmetic and food industries. [12][13][14] High-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS) routinely showed chemical composition varies between batches depending on raw materials and manufacturing processes. [15][16][17] In order to forecast biological properties, this research proposed a spectroscopic analysis of a cellular model using the comparative results of different extracted fractions on inflammatory induced macrophages.…”
Section: Introductionmentioning
confidence: 99%